Regulatory Effect of Resveratrol on Inflammation Induced by Lipopolysaccharides via Reprograming Intestinal Microbes and Ameliorating Serum Metabolism Profiles - Ding, Sujuan; Jiang, Hongmei; Fang, Jun; Liu, Gang (Frontiers in Immunology, 2021)
The purpose of this study was to explore the regulatory effect of resveratrol (RES) on lipopolysaccharide (LPS)-induced inflammation and its influence on intestinal microorganisms and serum atlas in murine models during the development of inflammation to explore a novel method for the regulation of inflammation. Mice were randomly assigned to three groups: control (CON), LPS, and RES–LPS. The results showed that RES mitigated the inflammatory damage to the intes-tines and liver induced by LPS. Compared with the LPS group, RES treatment decreased the levels of TNF-α, IL-6, IFN-γ, myeloperoxidase, and alanine aminotransferase in the liver. Serum metabolic profile monitoring showed that, compared with the CON group, LPS decreased the levels of five metabolites, including cycloartomunin and glycerol triundecanoate, and increased the levels of eight metabolites, including N-linoleoyl taurine and PE(O-16:0/20:5(5Z), 8Z, 11Z, 14Z, 17Z). Conversely, RES treatment increased the levels of eight metabolites, including pantothenic acid, homovanillic acid, and S-(formylmethyl)glutathione, and reduced seven metabolites, including lysoPE(20:4(8Z,11Z,14Z,17Z)/0:0) and 13-cis-retinoic acid, etc., in comparison with the LPS group. Moreover, RES treatment alleviated the negative effects of LPS on intestinal microbes by reducing, for instance, the relative abundance of Bacteroidetes and Alistipes, and increasing the relative abundance of Lactobacillus. These results suggest that RES has great potential for preventing in-flammation.